DISTRIBUTION, CHARACTERISTIC AND BEHAVIOR OF Rhinocypha anisoptera SELYS, 1879 (ODONATA: ZYGOPTERA: CHLOROCYPHIDAE) IN EAST JAVA - Muhammad Muhibbuddin Abdillah; Pungki Lupiyaningdyah (ZOO INDONESIA, 2020)
Rhinocypha anisoptera is distributed in Sumatra and Java. In Java, this species was previously recorded from Mount Wilis, Mount Arjuno, Mount Welirang, Mount Kawi, Nongkojajar, Mount Tengger, Mount Semeru, Ijen Crater and Baju-kidul, with most recent encounter at Mount Kelud. Despite the vast encounter localities, there was lack of specimens collected to reveal its typical characteristic and behavior. This study confirmed the existence of R. anisoptera at most localities in East Java as reported in 1934 by Lieftinck, with additional new distribution in Mount Anjasmoro. R. anisoptera is typically characterized by dark coloration at the hind wing leaving transparent in the bases with metallic blue-tinged covering 4–5 % area in mid-section of the hindwing. Differ from other Chlorocyphidae, R. anisoptera perch on leaves more frequently compared to perching on twigs and rocks near waterways.